Resenha crítica de CAPPELEN, Herman. Fixing Language: An Essay on Conceptual Engineering. Oxford: Oxford University Press, 2018. - Samuel Maia (Principia: An International Journal of Epistemology, 2021)
Resenha/Review de/of: Cappelen, Herman. Fixing Language: An Essay on Conceptual Engineering. Oxford: Oxford University Press, 2018.